The Secretome Derived From 3D-Cultured Umbilical Cord Tissue MSCs Counteracts Manifestations Typifying Rheumatoid Arthritis - Miranda, Joana P.; Camões, Sérgio P.; Gaspar, Maria M.; Rodrigues, Joana S.; Carvalheiro, Manuela; Bárcia, Rita N.; Cruz, Pedro; Cruz, Helder; Simões, Sandra; Santos, Jorge M. (Frontiers in Immunology, 2019)
Rheumatoid arthritis (RA) is an autoimmune disorder whose treatment is mostly restricted to pain and symptom management and to the delay of joint destruction. Mesenchymal stem/stromal cells from the umbilical cord tissue (UC-MSCs) have previously been proven to be immunomodulatory and more efficient than bone marrow-derived MSCs in causing remission of local and systemic arthritic manifestations in vivo. Given the paracrine nature of UC-MSC activity, their application as active substances can be replaced by their secretome, thus avoiding allogeneic rejection and safety issues related to unwanted grafting. In this work, we aimed at demonstrating the viability of applying the 3D-primed UC-MSC secretome for the amelioration of arthritic signs. A proteomics analysis was performed to both, media conditioned by UC-MSC monolayer (CM2D) and 3D cultures (CM3D). The analysis of relevant trophic factors confirmed secretome profiles with very significant differences in terms of therapeutic potential. Whereas CM3D was characterized by a prevailing expression of anti-inflammatory cytokines such as IL-10 and LIF, along with trophic factors involved in different mechanisms leading to tissue regeneration, such as PDGF-BB, FGF-2, I-309, SCF and GM-CSF; CM2D presented relatively higher levels of IL-6, MCP-1 and IL-21, with recognized pro-inflammatory roles in joint disease and pleiotropic effects in the progression of rheumatoid arthritis (RA). Accordingly, different motogenic effects over mouse chondrocytes and distinct capacities of inducing glycosaminoglycan synthesis in vitro were observed between CM3D and CM2D. Finally, the evaluation of arthritic manifestations in vivo, using an adjuvant-induced model for arthritis (AIA), suggested a significantly higher therapeutic potential of CM3D over CM2D and even UC-MSCs. Histological analysis confirmed a faster remission of local and systemic arthritic manifestations of CM3D-treated animals. Overall, the results show that the use of UC-MSC CM3D is a viable and better strategy than direct UC-MSC administration for counteracting AIA-related signs. This strategy represents a novel MSC-based but nonetheless cell-free treatment for arthritic conditions such as those characterizing RA.